Fear of Discovery Among Latino Immigrants Presenting to the Emergency Department. (13th February 2013) - Maldonado, Cynthia Z.; Rodriguez, Robert M.; Torres, Jesus R.; Flores, Yvette S.; Lovato, Luis M.; Goldstein, Joshua N.
Abstract Objectives Recent legislation mandating reporting of undocumented immigrants may instill fear of discovery when they access emergency department (ED) services. The objectives of this study were to: 1) characterize the knowledge and beliefs of undocumented Latino immigrants (UDLI) about health care workers' reporting (or nonreporting) of illegal immigrants in the ED, 2) determine whether UDLI fear discovery when presenting to the ED, and 3) determine the nature and sources of this fear. Methods This was a cross‐sectional study of UDLI and two comparison groups conducted in two California county EDs, from November 2009 to August 2010. The authors interviewed a convenience sample of adult UDLI, Latino legal residents (LLR), and non‐Latino legal residents (NLLR) using a structured instrument in their native language. The main outcome was fear of discovery among UDLI and the sources of that fear. Results Of 1, 224 patients approached, 1, 007 (82.3%) were interviewed: 314 UDLI, 373 LLR, and 320 NLLR. The median age was 43 years (interquartile range [IQR] = 31 to 55 years), and 51% were male. UDLIs were less likely to speak English (14%, 95% confidence interval [CI] = 10% to 18%), have health insurance (39%, 95% CI 32% to 44%), or have a regular primary care provider (PCP; 39%, 95% CI = 34% to 45%), compared to LLR (English 56%, 95% CI = 51% to 61%; health insurance 50%, 95% CI = 45% to 55%; regular PCP 51%, 95% = CI 46% to 57%) and NLLR (English 95%, 95% CI = 92% to 97%; health insurance 49%, 95% CI = 43% to 54%; regular PCP 51%, 95% CI = 45% to 56%). Of the 16% of UDLI who stated that nurses and doctors treat undocumented immigrant patients differently than citizens, 41% (95% CI = 29% to 54%) reported less respect given to UDLI by staff. Thirty‐two percent of UDLI had heard of Proposition 187, 13% believed hospital staff reported UDLI to immigration authorities, and 9% said they were asked about their citizenship status. Fear of coming to the hospital because of discovery was expressed by 12% (95% CI = 9% to 16%) of UDLI, with 42% (95% CI = 28% to 58%) citing discussions with friends/family, 32% (95% CI = 19% to 47%) citing media and 16% (95% CI = 7% to 30%) citing both as sources of this fear. Conclusions One in eight of UDLI presenting to the ED express fear of discovery and consequent deportation. Belief that medical staff report UDLI and recent immigration are risk factors for this fear. Family, friends, and media are the primary sources of these concerns.